Gaze-contingent manipulation of the FVF demonstrates the importance of fixation duration for explaining search behavior. (2017) - Laubrock, Jochen; Engbert, Ralf; Cajar, Anke
Abstract: Hulleman & Olivers' (H&O's) model introduces variation of the functional visual field (FVF) for explaining visual search behavior. Our research shows how the FVF can be studied using gaze-contingent displays and how FVF variation can be implemented in models of gaze control. Contrary to H&O, we believe that fixation duration is an important factor when modeling visual search behavior.